Results from the implementation of a protocol to improve mobilisation rates in a heterogeneous intensive care unit patient population - Harrold, M.; Webb, S.; Allison, Garry (2013)
Rationale: Critically ill patients receiving care in an intensive care unit (ICU) experience weakness of respiratory and skeletal muscle that is worse than that experienced by bed rest alone. This weakness is associated with an increased duration of mechanical ventilation and hospital length of stay. Mobilisation has been purported as a potential intervention to overcome this weakness. Currently, evidence for this treatment is based on physiological rationale and a small number of studies examining patients admitted predominantly for respiratory failure. It is not known if mobilisation levels can be increased for all patients admitted to ICU. Methods: The aim was to implement a systems change protocol that supported safe increases in mobilisation for all intensive care patients who were mechanically ventilated for three or more calendar day in a single centre. The design comparing prospective and retrospective cohort data sets involving all members of the multidisciplinary team. Mobilisation activities (sitting, standing, ambulation and utilising a tilt table), duration of mobilisation and associated physiological responses to mobilisation were recorde for consecutive patients. Results: A total of 1012 patients were studies: retrospective cohort – 498; practice audit – 102; and prospective cohort -412 patients. There was an across the board increase in the percent of patients mobilised from 63.3% to 79.9% (p = .002) after implementation of the program. Patients admitted with surgical (p = .048) or trauma (p = .001) diagnosis showed the greatest increase in the percent of patients mobilised. Adverse events were minimal (13 in 1855 activities) and none resulted in an increased length of stay. Conclusion: This study is the first to show it is both safe and feasible to increase mobilisation rates for all patients in an ICU with a multidisciplinary approach to system change.